Acute Traumatic Subdural Hematoma and Anticoagulation Risk. (3rd March 2023) - Kia, Maryam; Saluja, Rajeet Singh; Marcoux, Judith
ABSTRACT: Background: Anticoagulation is used to prevent thromboembolic events. It is a common practice to hold anticoagulation in the first few days following a traumatic brain injury (TBI) with intracranial hemorrhage. However, traumatic subdural hematomas (SDH) are prone to re-hemorrhage long after the trauma. Data are scarce in the literature on the best timing to resume anticoagulation following a TBI. Methods: Review of 95 consecutive patients admitted to a level 1 trauma center with a diagnosis of traumatic SDH and requiring anticoagulation. The reasons for anticoagulation, the amount of time without anticoagulation, CT characteristics, and the incidence of thromboembolic events or SDH re-hemorrhage were collected. Results: 41.3% used anticoagulation for coronary artery disease and peripheral vascular disease, 24% for atrial fibrillation, 12% for cardiac valve replacement, and 12% for venous thromboembolic events. Anticoagulation was held a median of 67 days. For most patients (82.1%), anticoagulation was re-introduced once the SDH had completely resolved. For 17.9%, anticoagulation was restarted while the SDH had not completely resolved. One (1.1%) patient suffered from an atrial clot while anticoagulation was held. For those with residual SDH, 41.2% suffered from a SDH re-hemorrhage and 17.6% required surgery. The risk of re-hemorrhage climbed to 62.5% if the SDH remnant was large. Conclusion: Anticoagulation while there is a residual SDH was associated with a significant risk of re-hemorrhage. This risk should be weighed against the risk of holding anticoagulation.